Aluminum Exposure in Neonatal Patients Using the Least Contaminated Parenteral Nutrition Solution Products - Poole, Robert L. (MDPI, 2012)
Aluminum (Al) is a contaminant in all parenteral nutrition (PN) solution component products. Manufacturers currently label these products with the maximum Al content at the time of expiry. We recently published data to establish the actual measured concentration of Al in PN solution products prior to being compounded in the clinical setting [1]. The investigation assessed quantitative Al content of all available products used in the formulation of PN solutions. The objective of this study was to assess the Al exposure in neonatal patients using the least contaminated PN solutions and determine if it is possible to meet the FDA “safe limit” of less than 5 μg/kg/day of Al. The measured concentrations from our previous study were analyzed and the least contaminated products were identified. These concentrations were entered into our PN software and the least possible Al exposure was determined. A significant decrease (41%–44%) in the Al exposure in neonatal patients can be achieved using the least contaminated products, but the FDA “safe limit” of less than 5 μg/kg/day of Al was not met. However, minimizing the Al exposure may decrease the likelihood of developing Al toxicity from PN.